SPSS SOFTWARE AS A TOOL FOR ANALYZING RELATIONSHIPS BETWEEN LECTURE PERFORMANCE AND STUDENT SUCCESFULL (Case Study) - Sundani, Dini (Jurnal Ilmiah Informatika Komputer, 2008)
One of the key factor that influenced the fulfillment of resources is the performance of individual (employee) in an organization. For educational organization, human resources are related to educative workforce (lecturer) and non-educative workforce. One of the objectives of educational organization is the succesfulness of the teaching-learning process. SPSS, in this case, is used to facilitate analysis. The effectiveness of learning is indirectly influenced by the performance of lecturers. This research is conducted to find the relation between factors in lecturer performance and learning effectiveness as well as the strength of the relation. Indicator for learning effectiveness is measured by students marks. Factors in lecturer performance include motivation and competence in teaching, where motivation is measured from teaching method and attendance. Performance measurement of lecturers is assessed by the student using survey. Survey data are tested by using validity test and reliability test. Method of analysis used in this research is statistical correlation techniques with non parametric method using Spearman rank correlation. The results show that there is a small and positive correlation between lecturer’s performance and learning effectiveness. Possitive relation with small value shows that, indirectly, the higher the lecturer’s performance the better the student’s succesfulness and, conversly, the lower the lecturer’s performance the worse the student’s succesfulness in learning process.Kata Kunci : keberhasilan belajar, kinerja dosen, korelasi SPSSSubject Description : K.3.Computeres and Education | K.3.1.Computer Uses in Education | Collaborative Learning